IMPLEMENTASI METODE MOORA (MULTI OBJECTIVE OPTIMIZATION ON THE BASIC OF RATIO ANALYSIS) UNTUK REKOMENDASI PEMILIHAN TYPE SEPEDA MOTOR TERBAIK (Studi Kasus : CV. Satu Hati Perkasa) - Nur ha yati (Universitas Islam Kuantan Singingi, 2020)
Motorcycle is one of the means of transportation that is loved by the community because it has a small size, fast and the price is not too expensive compared to other transportation equipment. Now many types of motorcycles complete with advantages and advantages. This of course will make it difficult for consumers to make the right choice, according to the desired criteria. To make it easier for buyers to choose the type of motorcycle that suits their needs, a decision support system is designed to recommend the appropriate motorcycle type.This system is built with accurate calculations using the MOORA method (Multi Objective Optimization on The Basic of Ratio Analysis) so that the accuracy of calculations is more guaranteed that is applied using PHP MySQL software. With this system, customers / buyers have no difficulty choosing the type of motorcycle that suits their needs and finances so that it will create a convenient and fast buying and selling process.From the 17 data, it can be seen that the results manually on the recommendation of a motorcycle type can be seen that A_3 is the highest alternative with a value of 27.336773. In other words the A_3 type motorcycle Vario 150 is the best motorcycle.